2023
DOI: 10.1002/ana.26788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotype of Pediatric and Adult Patients With Spinal Muscular Atrophy With Four SMN2 Copies: Are They Really All Stable?

Martina Ricci,
Gianpaolo Cicala,
Anna Capasso
et al.

Abstract: ObjectiveThe aim of this study was to provide an overview of the clinical phenotypes associated with 4 SMN2 copies.MethodsClinical phenotypes were analyzed in all the patients with 4 SMN2 copies as part of a nationwide effort including all the Italian pediatric and adult reference centers for spinal muscular atrophy (SMA).ResultsThe cohort includes 169 patients (102 men and 67 women) with confirmed 4 SMN2 copies (mean age at last follow‐up = 36.9 ± 19 years). Six of the 169 patients were presymptomatic, 8 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Looking at the age at which this loss of ambulation occurred, there was, as expected, a wide age range with a distribution that is relatively uniform. This observation largely confirms the findings documented in the comprehensive review by Wirth et al in 2021 [ 27 ] and the recent study by Ricci et al, who found an overall risk of walking loss of 35% in their cohort of SMA types 3 and 4 [ 16 ]. The time between "age at symptom onset" and "loss of ambulation" also showed a large variation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Looking at the age at which this loss of ambulation occurred, there was, as expected, a wide age range with a distribution that is relatively uniform. This observation largely confirms the findings documented in the comprehensive review by Wirth et al in 2021 [ 27 ] and the recent study by Ricci et al, who found an overall risk of walking loss of 35% in their cohort of SMA types 3 and 4 [ 16 ]. The time between "age at symptom onset" and "loss of ambulation" also showed a large variation.…”
Section: Discussionsupporting
confidence: 90%
“…There is a potential bias in the determination of the SMN2 copy number, as we know that especially the older determinations of the SMN2 copy number can be very inaccurate. It is therefore possible that not all patients have the correct copy number and that some patients with three copies may have been included, which was shown in the recent work by Ricci et al to be 10% in their 4 SMN2 copy cohort [ 16 ]. However, the observation that only 6.3% are ventilator dependent suggests that the substantial subset of patients with early motor symptoms from infancy have not been inadvertently included due to an incorrect copy number.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 149 In addition, recent work confirmed the variability of phenotypes in untreated patients with four copies of SMN2 , ranging from type 2 to type 4, and an overall reduction of functional scores with increasing age. 150 These findings indicate the importance of treating these patients earlier.…”
Section: Discussionmentioning
confidence: 93%